Pengaruh Disiplin Kerja, Pelatihan Kerja dan Fasilitas Kerja terhadap Prestasi Kerja Karyawan pada PT Kealyn Mandiri Sejahtera - Fauzan, Muhammad Oceano; Vera, Nevia Prima; Asria, Maya (Universitas Batanghari, 2024)
This study examines the factors that influence employee performance at PT. Kealyn Mandiri Sejahtera, namely work discipline, work training, and work facilities. The purpose of this study is to provide recommendations for the company and to increase insight for readers. The study was conducted by distributing questionnaires using the Likert Scale (1-5). The results showed a positive and significant influence between work discipline (X1) on performance (Y). Meanwhile, work training (X2) did not show a significant influence, and work facilities (X3) had a significant positive influence on performance (Y). Overall, a combination of good work discipline (X1) and work facilities (X3) had a significant influence on the performance (Y) of PT. Kealyn Mandiri Sejahtera employees.